2016
DOI: 10.1002/2016gl069166
|View full text |Cite
|
Sign up to set email alerts
|

MMS observations of large guide field symmetric reconnection between colliding reconnection jets at the center of a magnetic flux rope at the magnetopause

Abstract: We report evidence for reconnection between colliding reconnection jets in a compressed current sheet at the center of a magnetic flux rope at Earth's magnetopause. The reconnection involved nearly symmetric inflow boundary conditions with a strong guide field of two. The thin (2.5 ion‐skin depth (di) width) current sheet (at ~12 di downstream of the X line) was well resolved by MMS, which revealed large asymmetries in plasma and field structures in the exhaust. Ion perpendicular heating, electron parallel hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 38 publications
7
91
2
Order By: Relevance
“…Hence, we conclude that the bipolar structure detected at 14:16:40 UT was not caused by a vortex produced by the Kelvin‐Helmholtz instability. Another possibility is that the reconnecting current sheet was embedded in a macroscopic FTE, similar to that reported by Øieroset et al (). However, the bipolar signature in Øieroset et al () is in the magnetic field component normal to the MP, while in this case, the magnetic field rotation is in the Y GSM component, which is likely the tangential component of the MP as seen from the previous MP crossing at around 14:13 UT (see Figure ).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Hence, we conclude that the bipolar structure detected at 14:16:40 UT was not caused by a vortex produced by the Kelvin‐Helmholtz instability. Another possibility is that the reconnecting current sheet was embedded in a macroscopic FTE, similar to that reported by Øieroset et al (). However, the bipolar signature in Øieroset et al () is in the magnetic field component normal to the MP, while in this case, the magnetic field rotation is in the Y GSM component, which is likely the tangential component of the MP as seen from the previous MP crossing at around 14:13 UT (see Figure ).…”
Section: Discussionsupporting
confidence: 67%
“…Another possibility is that the reconnecting current sheet was embedded in a macroscopic FTE, similar to that reported by Øieroset et al (). However, the bipolar signature in Øieroset et al () is in the magnetic field component normal to the MP, while in this case, the magnetic field rotation is in the Y GSM component, which is likely the tangential component of the MP as seen from the previous MP crossing at around 14:13 UT (see Figure ). One possible explanation for the bipolar variation in B y is that the axis of the FTE is along Z GSM instead of in the X ‐ Y plane for a typical FTE at the low latitude MP.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, the coalescence of magnetic flux ropes has not been observed at the magnetopause. Most recently, Øieroset et al () found a strong ion jet within one flux rope at the magnetopause. By comparing with simulation results, they concluded that the ion jet in fact was created by reconnection occurring within the flux ropes.…”
Section: Discussion and Summarymentioning
confidence: 98%
“…With the Magnetospheric Multiscale Mission (MMS) data at the magnetopause, Øieroset et al . [] reported an ion jet within a large flux rope and suggested that it could be the result of the coalescence. So far, many questions on the coalescence remain, e.g., whether the coalescence can occur in the region away from the reconnection site and how long the coalescence can proceed.…”
Section: Introductionmentioning
confidence: 99%